Structural and functional dissection of the DH and PH domains of oncogenic Bcr-Abl tyrosine kinase - Sina Reckel (Nature Portfolio, 2017)
The Bcr-Abl tyrosine kinases p210 and p190 are linked to different leukemias and differ by the Dbl homology (DH) and Pleckstrin-homology (PH) domains. Here the authors characterize structures of the Bcr-Abl p210 DH and PH domains and find that the PH domain is important for the cellular localization and signaling network of p210.